O Povo and Diário do Nordeste: the news from Ceará periodicals as sources of study on AIDS in the early 1980s (Research, Society and Development, 2022)
This work sought to explore the meanings attributed to Acquired Immune Deficiency Syndrome (Aids) in the Ceará press, more specifically in two periodicals: O Povo and Diário do Nordeste, in the first four years of the 1980s, when the disease emerged as a real enigma for Science and that seemed to belong to specific groups and to spaces very far from Ceará. In this sense, the central question of this article is to show the content of the speeches given in the two Ceará periodicals during the years from 1982 to 1984, a period in which news about the disease began to be disseminated, which had not yet been reported in the “lands of Alencarinas”. Thus, from the analysis of these records that narrated their contemporaneity, the objective was to lay bare the representations of an unknown disease and the insecurity in the face of the little information that medicine could have at that moment about the disease and, mainly, about how to treat it.